Study of the effect of bacterial-mediated legume plant growth using bacterial strain Serratia marcescens N1.14 X-45 - Zheng, Jiaxin; Liu, Chao; Liu, Jiayi; Zhuang, Jia Yao (Frontiers in Microbiology, 2022)
Soil microorganisms play an indispensable role in plant growth and are widely used to promote plant growth. However, poor microbial strains are homogeneous. The heavy application of chemical fertilizers and pesticides to agricultural soil has adversely affected the soil flora, necessitating the regulation of the soil flora to maintain soil health. In this study, X-45, a highly efficient and phosphorus-dissolving strain of the lysogenic bacterium Serratia marcescens N1.14 was isolated from bare rock slope soil samples from Yueyang Avenue, Hunan Province, China. We observed that microbial strain X-45 could release P from the rocks into solution when the sample rocks were used as the only phosphorus source. Furthermore, we observed that the P content in media increased by 3.08 X compared to the control. After applying X-45 as a bacterial fertilizer, the growth of potted Indigofera pseudotinctoria plants significantly increased, the soil physicochemical properties were significantly improved, and the relative abundance of Bradyrhizobium in the soil increased significantly from 1 to 42%. Besides, Bradyrhizobium became the most dominant genus in the soil. The indirect promotion of another beneficial microorganism by X-45 further revealed the intrinsic mechanism by which X-45 exerted its effect on plant promotion and soil improvement. Using this bacteria, the hypothesis of the superposition effect of legume plant promotion was also confirmed.